What's New in Endocrinology?: The Hypothalamic Regulating Hormones - Killinger, D. W. (1975)
The clinical use of hypothalamic releasing hormones for diagnostic purposes has dramatically improved our understanding of the neural control of pituitary function. The potential therapeutic value of these compounds for treatment of infertility and hypogonadism will evolve in the near future. Analogues of LH-RH which antagonize LH-RH have been developed and may have a future role in fertility control. The clinical application of these hypothalamic hormones will evolve in the next few years.